The correlation between corona virus disease 2019 and alopecia areata: a literature review - Xie, Ying; Lv, Shuying; Luo, Sha; Chen, Yuxuan; Du, Meijiao; Xu, Yonglong; Yang, Dingquan (Frontiers in Immunology, 2024)
Corona virus disease 2019(COVID-19) is one of the most serious respiratory pandemic diseases threatening human health for centuries. Alopecia areata (AA) is a sudden patchy hair loss, an autoimmune disease, which seriously affects the image and mental health of patients. Evidence shows that the risk of autoimmune diseases significantly increases after COVID-19, and is positively correlated with the severity, with a significant increase in the risk of alopecia in those over 40 years old. The relationship between COVID-19 and AA has become a hot topic of current research. Strengthening the research on the correlation between COVID-19 and AA can help to identify and protect susceptible populations at an early stage. This article reviews the research progress on the epidemiological background of COVID-19 and AA, the situation and possible mechanisms of AA induced by COVID-19 or COVID-19 vaccination, and potential treatment methods.